Ultrasound and clinical characteristics of uterine smooth muscle tumors of uncertain malignant potential (STUMPs). (August 2020) - Cotrino, Ilenia; Carosso, Andrea; Macchi, Chiara; Baima Poma, Cinzia; Cosma, Stefano; Ribotta, Marisa; Viora, Elsa; Sciarrone, Andrea; Borella, Fulvio; Zola, Paolo
Highlights: Sonographic features of STUMPs may vary and histologic diagnosis is mandatory They are isoechoic lesions with regular borders, microcystic areas, no shadowing They can occur concurrently with myomas Abstract: Objective(s): Smooth muscle tumors of uncertain malignant potential are rare uterine neoplasms. Their identification through imaging is still limited due to the few available descriptions in the scientific literature. The objective of this paper is to provide clinical and ultrasound features that could support an early identification of these neoplasms. Study design: We retrospectively evaluated preoperative sonographic data of patients receiving a histopathological diagnosis of smooth muscle tumors of uncertain malignant potential between 2014 and 2019 at the S. Anna Hospital (Turin, Italy), a tertiary gynecological center. Tumors were characterized on the basis of ultrasound images using terms and definitions according to the morphological uterus sonographic assessment group. Results: A total of fourteen patients with smooth muscle tumors of uncertain malignant potential (20 lesions, including 18 pure and 2 with associated leiomyosarcoma) were identified. The median age was 47 years (range 28–77) and nine (64%) patients were of reproductive age. Six patients (43%) were asymptomatic, two (14%) presented with abdominal pain, two (14 %) with menorrhagia and four (29%) with both symptoms. Two (14%) patients developed local recurrences as uterine smooth muscle tumor of uncertain malignant potential and leiomyosarcoma, respectively. At ultrasound imaging, nine (69%) smooth muscle tumors of uncertain malignant potential were poorly or moderately vascularized and nine (82%) showed both circumferential and intra-lesional flows. Only three (15%) showed shadowing. The outlines were well-defined in seventeen cases (85%) and most (90%) showed isoechoic or mixed echogenicity with microcystic anechoic areas in fourteen (70%) of cases. Conclusion(s): Sonographic features of smooth muscle tumors of uncertain malignant potential may vary and a pathognomonic description has not been recognized. However, the identification of single or multiple lesions with specific ultrasound features should raise the suspicion of tumors of uncertain malignant potential. These features include isoechogenicity or mixed echogenicity, regular borders, presence of internal microcystic and anechoic areas, circumferential and intralesional vascularization ranging from minimal to high and absence of shadowing.